Development of a fast solver for moment-method based numerical electromagnetic codes - Zhao, Ruoqing. (2008)
In this thesis, intersubband absorption of Ino.53Gao.3Alo.17As/Ino.52Alo.48As multiple quantum well (MQW) structures using Fourier transform infrared (FTIR) spectrometry and its verification with photoluminescence (PL) and theoretical calculation are studied. Conduction band offset of the MQW derived from varying temperature I-V measurements, and characteristics of Ino.53Gao.12Alo.35As/Ino.52Alo.4sAs heterojunctions are also investigated